Functional dynamics to strengthen an agroecological technological innovation: the case of seedlings from stem fragments (PIF) plantain propagation technology in Cameroon - (:unkn) unknown (My University, 2022)
In Cameroon, plantain is crucial for food security but the planting material's production and purchase costs, his unavailability, and poor sanitary quality hindered its production's development. The agronomic research, through the African Regional Center of Research on Bananas and Plantains (CARBAP) installed in Cameroon, developed a planting material propagation technology innovation for banana plantain named seedlings from stem fragments (PIF) technique. This technique is still not widely used despite its great relevance to farmers and his agroecological potential. This paper questions the complementarity of the functions which support this innovation process and identifies perspectives of strengthening its utilization. Event History Analysis (EHA) methodology has served to identify the functions and their dynamic. Qualitative in-depth interviews and academic and non-academic literature were used as data. Three phases characterize the innovation process of the PIF technique from 1985 to 2022. The trajectory of the process shows that the collaborative method of technique's transfer was impeded by the fragmentation of the interventions. Then the innovation spreading is still incomplete. The establishment of a certification system for nursery trade are identified as reforms to be taken to return to a virtuous loop.
Keywords: African Research